Ответ:
2; 0.
Пошаговое объяснение:
Общий знаменатель:
[tex](\sqrt{5}+\sqrt{3})(\sqrt{5}-\sqrt{3})[/tex]
Раскрываем скобки:
[tex]\sqrt{5}^{2}-\sqrt{15}+\sqrt{15}-\sqrt{3}^2=\sqrt{5}^2-(-\sqrt{3})^2=5-3=2[/tex]
Упрощаем выражение:
[tex]\frac{(\sqrt{5}-\sqrt{3})(\sqrt{5}+\sqrt{3})-(\sqrt{5}+\sqrt{3})(\sqrt{5}-\sqrt{3})}{2}=\frac{\sqrt{5}^2+\sqrt{15}-\sqrt{15}-\sqrt{3}^2-(\sqrt{5}^2-\sqrt{15}+\sqrt{15}-\sqrt{3}^2)}{2}=\\=\frac{2-2}{2}=\frac{0}{2}=0\\0^2=0[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
2; 0.
Пошаговое объяснение:
Общий знаменатель:
[tex](\sqrt{5}+\sqrt{3})(\sqrt{5}-\sqrt{3})[/tex]
Раскрываем скобки:
[tex]\sqrt{5}^{2}-\sqrt{15}+\sqrt{15}-\sqrt{3}^2=\sqrt{5}^2-(-\sqrt{3})^2=5-3=2[/tex]
Упрощаем выражение:
[tex]\frac{(\sqrt{5}-\sqrt{3})(\sqrt{5}+\sqrt{3})-(\sqrt{5}+\sqrt{3})(\sqrt{5}-\sqrt{3})}{2}=\frac{\sqrt{5}^2+\sqrt{15}-\sqrt{15}-\sqrt{3}^2-(\sqrt{5}^2-\sqrt{15}+\sqrt{15}-\sqrt{3}^2)}{2}=\\=\frac{2-2}{2}=\frac{0}{2}=0\\0^2=0[/tex]